1997
DOI: 10.1007/pl00005002
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanides inhibit the human noradrenaline, 5-hydroxytryptamine and dopamine transporters

Abstract: Transporters for the monoamine neurotransmitters, including noradrenaline, 5-hydroxytryptamine [5-HT] and dopamine, have twelve transmembrane spanning regions and cotransport Na+ and Cl- ions. Another family of Na(+)-dependent transporters is that containing the Na+/glucose and Na+/proline cotransporters that are found in the epithelial cells of renal and intestinal brush border membranes. It has been shown that various trivalent lanthanides can substitute for Na+ for transport of glucose and proline. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In fact, mercury remains at least a potential contributing factor for autism [18], and should continue to be studied in that context. That having been said, however, it is important to note that a variety of metals such as lead, aluminum, cadmium, some of the lanthanides, copper and manganese (all multivalent cations) can negatively impact central dopamine metabolism[11, 53, 84, 95]. The fact that we were able to replicate the effects of mercury exposure by treating the animals with cadmium provides important support for the idea that it might be important to examine classes of environmental influences on the development of autism rather than looking for a specific cause.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, mercury remains at least a potential contributing factor for autism [18], and should continue to be studied in that context. That having been said, however, it is important to note that a variety of metals such as lead, aluminum, cadmium, some of the lanthanides, copper and manganese (all multivalent cations) can negatively impact central dopamine metabolism[11, 53, 84, 95]. The fact that we were able to replicate the effects of mercury exposure by treating the animals with cadmium provides important support for the idea that it might be important to examine classes of environmental influences on the development of autism rather than looking for a specific cause.…”
Section: Discussionmentioning
confidence: 99%
“…Rim et al (2013) identified the mean lethal dose (LD 50 ) of europium nitrate, chloride and oxide to be 320 mg/kg, 550 mg/kg and 5000 mg/kg respectively. In addition, the ionic species of Eu have been reported to inhibit the cellular uptake of norepinephrine, and inhibit calcineurin by replacing bound Ca 2þ (Ca 2þ /calmodulin-dependent phosphate) with Eu(III) (Burroughs et al, 1994;Bryan-Lluka and Bonish, 1997;Palasz and Czekaj, 2000).…”
Section: Introductionmentioning
confidence: 96%
“…Aiming to assess the NET‐recognizing ability of the benzylguanidine‐containing compounds L1 and metallated congener Tc1 , we have performed a cell uptake study in SH‐SY5Y cells. This cell line is a cloned subline of the neuroblastoma cells SK‐N‐SH that express monoamine transporters and were reported to take MIBG by an active mechanism . The results from this study indicated a moderate Tc1 uptake by SH‐SY5Y cells that increased as a function of incubation time at 37°C (Figure ).…”
Section: Resultsmentioning
confidence: 69%